PENGARUH PENDEKATAN SCIENTIFIC TERHADAP HASIL BELAJAR TEMATIK PESERTA DIDIK - SUBHANADRI SUBHANADRI (LP3M Universitas Muhammadiyah Muara Bungo, 2018)
This research starts from the problem of the lack of teachers involving students in learning, the lack of teachers in guiding students to do exercises, the lack of teachers explaining things that are difficult to understand by students. This results in low learning outcomes of students. This study aims to reveal the influence of the scientific approach on thematic learning outcomes in Class I State Elementary School 166 / II in Tirta Mulya Village, Bungo District. This research is a quasi-experimental study. The research design used in this study is the static camparison: randomized group control only design. Where in the two sample classes a different treatment was applied, in the experimental class the scientific approach was applied while in the control class a conventional approach was applied. The population in this study were all students of class I SD N 166 / II in the village of Tirta Mulya, Bungo Regency with samples of the IB class as the experimental class and IA class as the control class. Sampling is done randomly. Research data was collected through student learning outcomes tests. The proposed hypothesis was tested using the t-test. Based on the findings of the study and discussion, it was concluded that there were differences in learning outcomes of students who were taught using the scientific approach to learning outcomes of students who were taught using a conventional approach to integrated thematic learning. significant 5% is 1,645.